RNA stability is regulated by both RNA polyadenylation and ATP levels, linking RNA and energy metabolisms in Escherichia coli - Charlotte Roux; Marvin Ramos-Hue; Marjorie Audonnet; Marie-Pierre Duviau; Sébastien Nouaille; Agamemnon J. Carpousis; Sandrine Laguerre; Eliane Hajnsdorf; Muriel Cocaign-Bousquet; Laurence Girbal (mBio)
ABSTRACT The post-transcriptional process of RNA polyadenylation sits at the crossroads of energy metabolism and RNA metabolism. RNA polyadenylation is catalyzed by poly(A) polymerases, which use ATP as a substrate to add adenine to the 3′ end of RNAs, which can alter their stability. In Escherichia coli, RNA polyadenylation mediated by the major poly(A) polymerase was previously shown to facilitate degradation of individual RNAs. In this study, we performed the first genome-wide study of RNA stability in the absence of PAP I. Inactivation of the pcnB gene coding for PAP I led to the stabilization of more than a thousand of E. coli RNAs in the form of full-length functional molecules or non-functional fragments. The absence of PAP I altered the energy metabolism, with an almost 20% reduction in ATP levels. To better understand how RNA and energy metabolisms are interconnected, we investigated the role of ATP levels in regulating RNA stability. When we lowered intracellular ATP levels below 0.5 mM, many RNAs were stabilized, demonstrating the causal link between ATP levels and RNA stability for the first time in E. coli. Above this concentration, changes in ATP levels had no impact on RNA stability. We also demonstrated that some RNAs were stabilized when PAP I was inactivated by low ATP availability. These results clearly demonstrate that PAP I mediates an energy-dependent RNA stabilization, which may contribute to cell energy homeostasis under energy-limited conditions.IMPORTANCEPoly(A) polymerases are prime targets for understanding the interactions between RNA polyadenylation, RNA stability, and cellular energy. These enzymes catalyze the process of RNA polyadenylation, which involves ATP hydrolysis and addition of poly(A) tails to the 3′ end of RNAs. 3′ end poly(A) extensions potentially facilitate RNA degradation in bacteria. In this study, we inactivated the pcnB gene encoding PAP I, the major poly(A) polymerase in E. coli, and investigated the effects on RNA stability and energy levels. Our results show for the first time in E. coli a genome-wide RNA stabilization in the absence of PAP I associated with a decrease in ATP levels. We provide the first evidence in E. coli of a link between ATP levels and RNA stabilization and demonstrate that this is mediated in some cases by PAP I. PAP I-mediated RNA stabilization at low ATP levels could be a means of energy conservation under energy-limited conditions.